Clinical and mutational spectrum of limb-girdle muscular dystrophy type 2I in 11 French patients. Issue 12 (16th November 2009) - Bourteel, H; Vermersch, P; Cuisset, J-M; Maurage, C-A; Laforet, P; Richard, P; Stojkovic, T
Abstract : Background: Limb-girdle muscular dystrophy 2I (LGMD2I) is caused by mutations in the fukutin-related protein gene FKRP, which is also involved in congenital muscular dystrophy (MDC1C). Objective: To evaluate the clinical, biological, radiological and mutational characteristics of LGMD2I patients with FKRP mutation. Methods: Eleven patients from nine families from the north of France were studied. Demographical data, muscular testing results, cardiac and respiratory examinations, muscle histological features and a genetic analysis of the FKRP gene for each patient are reported. Eight patients underwent brain MRI and seven neuropsychological tests. Results: The patients included six women and five men. The mean age at onset was 9 years (range 1.5 to 23 years). Five patients remained self-ambulatory, whereas the other six were confined to a wheelchair by a mean age of 19 years, after a mean disease duration of 10 years. Nine patients suffered from restrictive respiratory insufficiency, and two male patients had severe dilated cardiomyopathy. Neuropsychological tests revealed memory impairment in four cases. Brain MRI revealed cerebral abnormalities in four patients (4/8). Ten patients were carriers of the common L276I mutation, which was either homozygous (four patients) or heteroallelic with another mutation (six patients). Among the mutations found, three were novel: L322V, L489R and R275G. Conclusions: This study reveals inter- and intrafamilial phenotypic variability in LGMD2I, with a preponderance of myocardiopathy and restrictive respiratory insufficiency. It also demonstrates central nervous involvement, probably associated with changes in α-dystroglycan expression in the brain.